SILVER NANOPARTICLES: PREPARATION AND USE FOR MEDICAL PURPOSES - I. E. Stanishevskaya; A. M. Stoinova; A. I. Marakhova; Ya. M. Stanishevskiy (Разработка и регистрация лекарственных средств, 2019)
Currently nanotechnologies have a significant impact on the development of medicine. Silver nanoparticles is one of the most widely studied objects nanotechnology. The methods of preparation of silver nanoparticles. Examples of the use of silver nanoparticles in medicine and pharmacy.